The problem of arbitrariness in employer decisions An analytical study in light of the theory of abuse of rights - Omed Aziz Ismail (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
This article aims to indicate the potentiality of implementing “abuse of rights” theory to evaluate the employer’s decisions that would be taken within an enterprise. Even though the employer has a widen rights and authorities to manage his/her enterprise, the exercise of those authorities may lead to arbitrariness. The employer’s decision might be contradicted directly with the employee’s interest, such as the decision of transferring an employee, and the decision of terminating the employment contract during or after the probation period. The same conflict can be occurred indirectly between the employee and the employer, when the later decide to shrink the enterprise or close it entirely, that lead to terminate the employment contract. However, the employer, in such the previous situations, can appeal the decision and ask the court to invalidate it if there is arbitrariness in taking the decision, such as in the case unjustified termination. And then, the court may investigate about the validity of the decision depending on the standards of abuse of rights theory, especially, in the case of the absence of legal texts.